Investigation of main characteristics of frequency multipliers in the range of 120-220 GHz - M. A. Borovskaya; V. P. Lipatnikov; M. M. Kasperovich; A. M. Kostrikin; A. V. Gusinskiy (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The features of the design and the operation principle of frequency doublers in range 120-220 GHz are considered. The results of input and output power measurements of frequency doublers are given, the values of them efficiency factors are calculated. A technique for measuring and estimating the results of the deviation of the efficiency is developed. The dependence of the transmission coefficients from the value of the output power of the frequency doublers is investigated.